2021
DOI: 10.1038/s42003-021-02324-6
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent shift in the de novo proteome accompanies pathogenesis in an Alzheimer’s disease mouse model

Abstract: Alzheimer’s disease (AD) is an age-related neurodegenerative disorder associated with memory loss, but the AD-associated neuropathological changes begin years before memory impairments. Investigation of the early molecular abnormalities in AD might offer innovative opportunities to target memory impairment prior to onset. Decreased protein synthesis plays a fundamental role in AD, yet the consequences of this dysregulation for cellular function remain unknown. We hypothesize that alterations in the de novo pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 87 publications
1
14
0
Order By: Relevance
“…Similarly to our study, cytoskeletal integrity, mitochondrial function, protein turnover and cell signalling were the cellular functions more heavily affected. Other recent proteomics studies on the hippocampus of the APP/PS1 mouse model of AD show similarities with our results, with changes in proteins involved in protein turnover pathways (both synthesis and degradation) [ 52 , 53 ], neurotransmission [ 52 ], and, importantly, oxidative stress [ 53 ]. A key result of our proteomics study is in fact the identification of expression changes for proteins and enzymes associated with redox homeostasis, which suggests the possibility that the brain accumulation of amyloid peptide β leads to oxidative stress.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly to our study, cytoskeletal integrity, mitochondrial function, protein turnover and cell signalling were the cellular functions more heavily affected. Other recent proteomics studies on the hippocampus of the APP/PS1 mouse model of AD show similarities with our results, with changes in proteins involved in protein turnover pathways (both synthesis and degradation) [ 52 , 53 ], neurotransmission [ 52 ], and, importantly, oxidative stress [ 53 ]. A key result of our proteomics study is in fact the identification of expression changes for proteins and enzymes associated with redox homeostasis, which suggests the possibility that the brain accumulation of amyloid peptide β leads to oxidative stress.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our study, IEGs/transcription factors were prominent in the upregulated genes (for example, FOS and EGR-1), as well as NFk-B and CREB regulated genes, whereas at 2 h, inflammatory response regulation was the most significant biological function of the highest scoring network. A recent mouse proteomic study comparing an AD model and healthy controls identified protein members for similar family group as this study (splicing factors, ribosomal proteins, proteasome, chaperones, syntaxins, and solute carrier proteins) ( Elder et al, 2021 ). A genome wide association study (GWAS) identifying AD risk genes highlighted 11 causal genes, 4 of which were found in this study [sortin, nexin, syntaxin, and pleckstin homology domain proteins ( Wingo et al, 2021 )].…”
Section: Discussionmentioning
confidence: 75%
“…Intriguingly, altered expression of rRNA and mRNAs coding for ribosomal proteins are documented to occur presymptomatically in AD (Ding et al, 2005(Ding et al, , 2006Hernández-Ortega et al, 2016). Accordingly, studies have revealed a dysregulation of de-novo protein synthesis in AD (Cefaliello et al, 2020;Elder et al, 2021) as well as in other forms of taupathies (Moreno et al, 2013;Radford et al, 2015;Meier et al, 2016;Evans et al, 2019;Koren et al, 2019). Along with basal translation, defects in synaptic activity mediated signaling and translation is also reported to occur presymptomatically in AD (Ma et al, 2010;Yang et al, 2016;Ahmad et al, 2017;Cefaliello et al, 2020).…”
Section: Introductionmentioning
confidence: 99%